The Optimization of Bawaslu’s Role in the 2024 Simultaneous Elections: Optimalisasi Peran Bawaslu dalam Pemilu Serentak 2024 - Shalihah, Aini; Huroiroh, Ernawati (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
Election Supervisory Body (Bawaslu) plays a vital role in ensuring that elections in Indonesia are conducted in compliance with legal regulations. The complexity of implementing simultaneous elections is a challenge for Bawaslu as one of the core institutions in the 2024 simultaneous election process, requiring strict adherence to the provisions set forth in Law No. 7 of 2017 on Elections. This study examines how Bawaslu can optimize its oversight role in the 2024 simultaneous elections and explores its authority in managing this electoral process. Using a normative juridical approach, the study finds that Bawaslu has effectively strengthened its capacity to fulfill its duties and functions in line with its founding objectives. Bawaslu’s optimization efforts include issuing updated Bawaslu Regulations (Perbawaslu) and implementing refined operational mechanisms, which aim to ensure a smooth electoral process that aligns with constitutional mandates.